Beating stress: music with monaural beats reduces anxiety and improves mood in a non-clinical population - Venkatesan, Tara; Demetriou, Andrew; Koops, Hendrik Vincent; Bowling, Daniel L. (Frontiers in Psychology, 2025)
Auditory beat stimulation in the delta–theta frequency range (0–7 Hz) is gaining interest as a non-invasive intervention for anxiety. This study investigated the effects of a relatively understudied form—monaural beats—and whether they produce acute changes in anxiety and mood when presented alone or embedded harmonically within music. Participants (n = 308) were randomly assigned to one of three 30-min listening conditions: (1) Monaural Beats + Music, (2) Monaural Beats-Only, or (3) a Pure Tone Control. Psychological effects were assessed via changes in self-reported anxiety (State–Trait Anxiety Inventory, state subscale) and mood (bipolar Likert scales for emotional valence, arousal, and energy). The results showed that only the Beats + Music condition significantly reduced anxiety from before to after listening with a medium effect size anxiety from before to after listening (p < 0.001, d = −0.58). Furthermore, only the Beats + Music significantly increased emotional valence from before to after listening (p < 0.001, d = 0.48). Finally, the Beats-Only condition showed a significant reduction in energy from before to after listening (p < 0.05, d = −0.28). These findings indicate that monaural beats can be harmoniously integrated into music without diminishing the anxiolytic properties of the latter, whereas presentation of beats alone has different effects. This suggests that integrating monaural beats within music may be a viable approach for targeted auditory neuromodulation.